Reflection of green marketing in perceived customer value: An applied study at Al-Zahrawi Surgical Hospital (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research aims to test the impact of green marketing in its dimensions (green product, green pricing, green distribution, green promotion) on the perceived value of the customer in its dimensions (functional, emotional, and social), in Al-Zahrawi Surgical Hospital in the State of Iraq. The research problem was represented by the question that states: The effect of green marketing activities on the perceived value of the customer in Al-Zahrawi Surgical Hospital. “The research relied on two main hypotheses with the correlation test and one for the simple linear regression test to explore and treat the research problem. As for the research sample, it was represented by (220) individuals from doctors, nurses, and administrators from the researched hospital’s staff. The questionnaire was used as a main tool for collecting data prepared by the researcher based on ready-made measures, and the researcher adopted a set of statistical methods, including (the arithmetic mean, standard deviation, coefficient of variation,), and the data were analyzed through the use of statistical programs (SPSS V.24), The research adopted the descriptive analytical method. Among the most prominent results that have been reached is the existence of a statistically significant correlation and impact relationship between the green marketing variable with its dimensions (green product, green pricing, green distribution, green promotion) in the perceived value of the customer in its dimensions (functional, emotional, and social). The research concluded with a set of recommendations. The most important of which is the necessity to activate the role of external and internal oversight committees to assess green orientation measures in health services provided by hospitals and prices in line with international standards.